FAKTOR YANG MEMPENGARUHI TINGKAT KETIMPANGAN PENGELUARAN PENDUDUK INDONESIA - Wulan Nur Yulianingdyah (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the inequality of population spending in Indonesia. The variables used are HDI, percentage of poor people, TPT, and GRDP per Capita and investment. This study uses multiple regression analysis, Spatial Autoregressive (SAR) Model, and Spatial Error Model (SEM). The criteria for the goodness of the model used is to compare the R2 and AIC values ​​of the two models. The best models are those with higher R2 and lower AIC than other models. This study concludes that the distribution pattern of the Gini ratio in Indonesia appears to be clustered between adjacent areas. Based on the relationship between the Gini ratio and HDI, the percentage of poor people, TPT, GRDP per capita, and investment, it can be interpreted that the similarities and differences in characteristics in each adjacent province can lead to an increase or decrease in the Gini ratio/level of expenditure inequality in Indonesia. The SEM regression model is better than the OLS regression model in determining the factors that influence the level of expenditure inequality in Indonesia because there is a spatial dependency on the dependent variable. In the SEM model, the variables that have a significant effect on the Gini ratio are HDI, percentage of poor people, and investment.